High‐throughput genome editing in rice with a virus‐based surrogate system. Issue 3 (31st December 2022) - Tian, Yifu; Zhong, Dating; Li, Xinbo; Shen, Rundong; Han, Han; Dai, Yuqin; Yao, Qi; Zhang, Xuening; Deng, Qi; Cao, Xuesong; Zhu, Jian‐Kang; Lu, Yuming
ABSTRACT: With the widespread use of clustered regularly interspaced palindromic repeats (CRISPR)/CRISPR‐associated nuclease (Cas) technologies in plants, large‐scale genome editing is increasingly needed. Here, we developed a geminivirus‐mediated surrogate system, called Wheat Dwarf Virus‐Gate (WDV‐surrogate), to facilitate high‐throughput genome editing. WDV‐Gate has two parts: one is the recipient callus from a transgenic rice line expressing Cas9 and a mutated hygromycin‐resistant gene ( HygM ) for surrogate selection; the other is a WDV‐based construct expressing two single guide RNAs (sgRNAs) targeting HygM and a gene of interest, respectively. We evaluated WDV‐Gate on six rice loci by producing a total of 874 T0 plants. Compared with the conventional method, the WDV‐Gate system, which was characterized by a transient and high level of sgRNA expression, significantly increased editing frequency (66.8% vs. 90.1%), plantlet regeneration efficiency (2.31‐fold increase), and numbers of homozygous‐edited plants (36.3% vs. 70.7%). Large‐scale editing using pooled sgRNAs targeting the SLR1 gene resulted in a high editing frequency of 94.4%, further demonstrating its feasibility. We also tested WDV‐Gate on sequence knock‐in for protein tagging. By co‐delivering a chemically modified donor DNA with the WDV‐Gate plasmid, 3xFLAG peptides were successfully fused to three loci with an efficiency of up to 13%. Thus, by combining transiently expressed sgRNAs and a surrogate selection system, WDV‐Gate could be useful for high‐throughput gene knock‐out and sequence knock‐in. Abstract : The new high‐throughput genome editing method, called WDV‐Gate, consists of a transgenic rice line expressing a mutated hygromycin‐resistant gene for surrogate selection and a geminivirus‐based construct expressing sgRNAs of CRISPR/Cas9, and achieved large‐scale genome editing using pooled sgRNA libraries.